Effectiveness of Using CANVA Application as a Learning Media for Creative Products and Entrepreneurship - Vetta Darmi Yetti; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This article aims to describe the effectiveness of using Canva as a medium forlearning creative products and entrepreneurship in vocational high schools.Globalisation brings major changes in the order of life of society. Thesechanges are driven by the development of science and technology, which hasan impact on various sectors of life including education. The design of learningmedia at this time does not only utilise objects that can be found in everydaylife but also utilise the digital world. Canva is an application that can bedeveloped in the process of making learning media for creative products andentrepreneurship which really needs media as an introduction to informationfrom abstract learning material content. The Canva application provides avariety of interesting features that can facilitate teachers in making learningmedia, one of which is the availability of various templates that can be used inthe process of designing learning media, one of which is the subject of creativeproducts and entrepreneurship in vocational high schools. In theimplementation of this research, the literature review method is used, namelyby the process of laying, obtaining, reading, and evaluating various researchliterature related to or related to the issues to be studied. The data described arethe results of research on the effectiveness of using the Canva application thathas been carried out by previous researchers.